Rock weathering creates oases of life in a High Arctic desert - F. Mapelli; S. Borin; F. Tambone; R. Marasco; B. Scaglia; f. Adani; D. Daffonchio; S. Ventura; L. Brusetti; F. Schubotz; L. P. D’ Acqui; B. Solheim; et al. (2010)
Several mechanisms occurring in terrestrial environments are still poorly understood like those driving soil formation and primary colonization by plants (Hodkinson et al., 2002). Moraines indicate any glacially-formed accumulation of unconsolidated rock debris that occur in currently or formerly glaciated regions. Polar moraines above the 75° are classified as cold desert since for most of the year water is immobilized as ice and precipitations are rare. In polar moraines photosynthesis by cyanobacteria and microbial heterotrophic assimilation of organic materials released by animals or transported by wind are commonly considered the processes initiating soil genesis and mediating plant colonization (Hodkinson et al., 2003). In this work we demonstrated that pyritic rock mineral weathering mediated by chemolithoautotrophic bacteria is associated to plant community formation in sites recently released by permanent glacier ice cover in the Midtre Lovénbreen glacier moraine (78°53’N), Svalbard. Increased soil fertility fostered the growth of prokaryotes and plants at the boundary between sites of intense bacterial mediated chemolithotrophic iron-sulfur oxidation and pH decrease, and the common moraine substrate where carbon and nitrogen are fixed by cyanobacteria. Rock pyrite weathering mediated by Acidithiobacillus ferrooxidans determined acidity and corresponding fertility gradients, where water retention, cation exchange capacity and nutrient availability were increased. The interaction between microorganisms and moraine minerals determined a peculiar, not yet described model for soil genesis and plant ecosystem formation with potential, past and present, terrestrial and extraterrestrial analogues in other harsh environments with similar geochemical settings.